Support Factors and Mechanisms for Civil Servants’ Digitalization Readiness - Pulkkinen, Jarmo; Suhonen, Marjo; Leinonen, Jaana (Scandinavian Journal of Public Administration, 2025)
This study investigates organizational support factors and mechanisms that enable civil servants' digitalization readiness in municipal technical services. We define civil servants' digitalization readiness as an individual's ability and preparedness to utilize devices, software, digital materials, and remote work in their public organization duties. Despite increasing digitalization in public administration, there is limited understanding of how civil servants experience and perceive organizational support in the digitalization context, particularly in the technical sector, where digital transformation significantly impacts service delivery. Empirical data was collected through individual thematic interviews with civil servants in land use planning and construction supervision in 11 Finnish municipalities. We identified two mechanisms enabling civil servants’ digitalization readiness: (1) organizational resource mechanism, where socio-technical resources (e.g., infrastructure, peer support, IT support, and data management) affect work capabilities, and (2) creative digital tension mechanism, which activates through drivers including peer examples, skills assessments, state legislation, and perceptions of usefulness. Creative digital tension emerges as civil servants recognize gaps between current and desired capabilities, motivating learning and utilization of technologies. Our primary contribution to public administration literature is developing a conceptual framework for understanding organizational support mechanisms for civil servant digitalization readiness in municipal service production digital transformation.